Backing environmental innovations through information technology adoption. Empirical analyses of innovation-related complementarity in firms - Antonioli, Davide; Gilli, Marianna; Mazzanti, Massimiliano; Nicolli, Francesco (Technological and Economic Development of Economy, 2018)
The paper tests empirically whether various types of Information and Communication Technologies (ICT) adoption and other innovation practices (techno-organisational change and training courses) are complementary inputs with respect to the adoption of specific environmental innovations (EI). The analysis is based on original survey data for a large industrial Italian region (Emilia-Romagna), which offer various views on ICT and EI relationships. This survey contains information on the adoption of environmental innovations and some detailed information on ICT issues and other technological-organisational processes. Our main findings suggest that, overall, complementarity does not seem to characterize the relationship between ICT and other innova-tion processes as a force behind environmental innovation, but some important exceptions emerge. Complementarities exists, for instance, between technological innovation and both adoption of ICT management systems and ICT for cooperation with clients. Interestingly, restricting the analysis to a sub-sample of more polluting firm, both complementarity and substitutability emerge more evidently.First published online 14 April 2016